The Relationship of Nutrition Knowledge, Nutritional Intake, and Physical Activity with Adolescent Nutritional Status - Ulfah, Maria; Hariati, Niken Widyastuti; Abdurrachim, Rijanti (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
Adolescence is a transitional period vulnerable to nutritional problems due to physical changes and lifestyle patterns. Data from July 2025 involving 91 adolescents at PPRSAR Mulia Satria showed varied nutritional status ranging from severely underweight to obese. This study aimed to analyze the relationship between nutritional knowledge, dietary intake, physical activity, and nutritional status. A cross-sectional study was conducted from October to November 2025 involving 91 adolescents. Dietary intake was assessed using a non-consecutive 2×24-hour food recall, physical activity using PAQ-A, and nutritional status based on WHO 2007 BMI-for-age standards. Data were analyzed using the Chi-Square test. The results showed a significant association between dietary intake and nutritional status, while nutritional knowledge and physical activity were not associated. It is concluded that dietary intake is the main determinant of adolescents’ nutritional status.